Farmer’s Survey and Monitoring of Fruit Flies (Diptera: Tephritidae) in Citrus Orchards of Ramechhap District, Nepal - Karki, Bipin; Thapa, Resham Bahadur; Adhikari, Debraj; Gautam, Bhola; Shedai, Amrita (Journal of the Plant Protection Society, 2023)
Fruit flies (Diptera: Tephritidae) are devastating pests in citrus orchards of Nepal causing huge losses of fruits. A farmer's survey was carried from March to December, 2021 randomly selecting 40 citrus orchard owners, and at the same time, a field monitoring of fruit flies organised in randomized complete block design with 7 times replicated 3 treatments (Cue lure and malathion in Steiner trap, Methyl eugenol and malathion in Steiner trap and protein bait in McPhail trap) were conducted in Ramechhap district of Nepal. Survey revealed that Chinese citrus fly was the most problematic insect pest of citrus orchard. However, only few farmers were practising effective control measures against this pest. Nine species of fruit flies were trapped in different lures and protein bait, when the number of fruit flies differed significantly (p<0.05) except Bactrocera correcta and Zeugodacus cucurbitae, which were found attracted in negligible number in Methyl eugenol and Cue lure, respectively. Z. scutellaris, Z. tau, B. nigrofemoralis were attracted to Cue lure. B. dorsalis and B. zonata were attracted to Methyl eugenol and B. minax, B. nigrofemoralis and Dacus sphaeroidalis were attracted in protein bait. The study concluded that the male lures and protein bait were useful to monitor specific fruit fly species in citrus orchards, hence their management strategies should be made accordingly.